Predictors of Loneliness among Older Adults in South-Eastern Nigeria: Implications for Social Workers (European Journal of Mental Health, 2021)
Old-age loneliness is a crucial public health issue with mortality consequences as well as other negative health conditions and lifestyles including depression, substance abuse, sedentary lifestyles, and suicide ideation. This study investigated the predictors of loneliness among older adults in Nigeria’s southeast in order to articulate some interventions that will plummet the issue. A structured questionnaire (N = 516), in-depth interviews (N = 8), and focus group discussion (N = 16) were used to collect data from respondents aged 60 years or older. The quantitative data sets were subjected to chi-square and binary regression analysis, while a thematic analysis was adopted for the qualitative data. The study’s findings show that some demographic factors such as the number of children (p < .002), health status (p < .023), and social support (p < .014), among others, were statistically significant in predicting loneliness among older adults. The study, therefore, recommends the consideration of community-based services to enable elderly adults to buffer the experience of loneliness. Social workers should also influence the various organs responsible for social policies to formulate and promote policies that address the well-being of older adults.